2018
DOI: 10.1038/s41419-018-1129-1
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in depression: a potential therapeutic target

Abstract: Leptin, produced and secreted by white adipose tissue, plays a critical role in regulating body weight, food intake, and energy metabolism. Recently, several studies have identified an underlying role for leptin in regulation of mood and cognition via regulation of synaptic changes in the brain that have been associated with antidepressant-like actions. Brain neural plasticity occurs in response to a range of intrinsic and extrinsic stimuli, including those that may mediate the effects of antidepressants. Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 102 publications
2
59
0
1
Order By: Relevance
“…Thus, leptin signaling stimulates pro-inflammatory cytokine secretion and influences cortisol release, serotonin and dopaminergic pathways, brain-derived neurotrophic factor (BDNF) signaling and hippocampal synaptic plasticity [93]. Altered leptin levels have been implicated in depression [94]. Elevated early childhood leptin levels in plasma, but not in cord blood, have been associated with an increased risk for autism [95], and associations between leptin levels and other behaviors have been reported from rodent models [93].…”
Section: Metabolic Hormonesmentioning
confidence: 99%
“…Thus, leptin signaling stimulates pro-inflammatory cytokine secretion and influences cortisol release, serotonin and dopaminergic pathways, brain-derived neurotrophic factor (BDNF) signaling and hippocampal synaptic plasticity [93]. Altered leptin levels have been implicated in depression [94]. Elevated early childhood leptin levels in plasma, but not in cord blood, have been associated with an increased risk for autism [95], and associations between leptin levels and other behaviors have been reported from rodent models [93].…”
Section: Metabolic Hormonesmentioning
confidence: 99%
“…Modifications of leptin metabolism and its gene expression, as well as its receptor, have been reported among patients with mental health disorders, independently to psychotropic drugs or in absence of antipsychotics [43]. Several studies showed a particular interest in the relationship between leptin and depressive disorders, but with discordant conclusions [42][43][44][45].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 99%
“…If increased leptin occurs in the absence of satiety behaviours, but rather in association with depressogenic increased eating corresponding to leptin resistance, this may be a potential therapeutic target to address problematic eating and weight gain risk in a large subset of individuals with MDD, particularly females. The potential of leptin as a therapeutic target for other symptoms in MDD is currently being considered (Ge et al, 2018), however its potential role in weight gain associated with MDD has received little consideration to date.…”
Section: Discussionmentioning
confidence: 99%